Postoperative Fluid Management in Emergency Abdominal Surgery in Omdurman Teaching Hospital - Elbashier, Omer ElgorashiAbdelrahim; Hamza, Aamir Abdullahi (مجلة الجزيرة للعلوم الصحية; مجلد 15 عدد 1 (2019), 2019)
Background: Postoperative intra-venous (IV) fluid management is still challenging, and despite many well-established guidelines, there are defects in IV fluid therapy. Many studies have shown that mal practice is not uncommon. An individualized approach in choosing types and amounts of IV fluid that meet the patient’s needs, is being advocated. Complications of IV fluid management are common, and might be life-threatening, causes are: mismanagement, mal documentation and poor assessment. Objectives: In this study, we reported the postoperative fluid management in emergency laparotomy at Omdurman teaching hospital Patients and methods: This cross-sectional prospective study included 87 patients. All patients with emergency laparotomy who received postoperative IV fluids, in Omdurman teaching hospital, between April 2018 and March 2019 were enrolled. Results: Age of patients range from 18 to 78 years.Males; 69 (79.3%) and females; 18 (20.7%). Most common cause for emergency laparotomy was penetrating abdominal trauma (36.8%), peritonitis (25.3%), Intestinal obstruction (21.8%), and blunt abdominal trauma (16.1%). Minimum amount given was 3 liters, and maximum amount was 6 liters. The most common type used is D5%, RL, DNS then NS. There were no weight measurements and fluids were seldom given in relation to weight or age. Overload occurred in (43%) of patients, under-hydration in (61%) of patients and electrolyte imbalance in (42.5%) of patients. Hypernatraemia developed in (27.6%) patients, and was related to overprescribing of high doses of saline-contained fluids (>250mmol/day) in about (87.5%) of patients.Fluid overload was related significantly to hypernatraemia. Hypokalaemia developed in (14.9%) of patients which was related to lack of potassium supplementation in all cases. Conclusion: Malpractice of postoperative fluid management was common in patients who underwent emergency laparotomy in Omdurmanteaching hospital. Simple interventions might be introduced to improve outcomes such as training and education in this domain.